ANALISIS LITERASI DIGITAL APARATUR DESA DALAM PENGUATAN PELAYANAN PUBLIK WILAYAH PERBATASAN 3T: DESA RAE INDUK, KABUPATEN KEPULAUAN TALAUD - Jegiftha Victoria Putri Pratami Lumettu; Anggita Chairiah; Lulu Qurrata A'yun; Echlesia Apita; Melan Y Panditan; Atriani V Manurat (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Digital transformation has become an important agenda in public sector governance, including at the village government level. The implementation of digital-based public services requires village officials to possess adequate digital literacy to effectively utilize information and communication technologies in administrative and service processes. However, the digital divide remains a significant challenge in border, frontier, and disadvantaged regions where limitations in infrastructure, internet access, and human resource capacity often hinder the optimization of digital governance. Despite the growing body of research on digital literacy and village digitalization, studies focusing on the digital competencies of village officials in border areas remain relatively limited. This study aims to analyze the digital literacy of village officials and its contribution to strengthening public services in Rae Induk Village, Talaud Islands Regency, one of Indonesia’s border regions. A qualitative descriptive approach was employed through in-depth interviews, observation, and documentation involving government officials and community members as research informants. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that village officials generally possess basic digital competencies in operating computers, internet services, electronic mail, and digital administrative applications. Nevertheless, the implementation of digital public services is still constrained by limited internet connectivity, inadequate technological infrastructure, and disparities in digital skills among officials. Strengthening digital literacy has contributed to improving administrative efficiency, data management, service accessibility, and transparency. Therefore, continuous capacity-building programs, infrastructure improvement, and policy support are essential to accelerate inclusive digital transformation and enhance public service quality in border villages. Keywords: Digital Literacy; Village Officials; Public Service; Border Village; Talaud Islands